1993
DOI: 10.1139/f93-063
|View full text |Cite
|
Sign up to set email alerts
|

Localisation cytologique du cuivre et de quelques autres métaux dans la glande digestive de la seiche, Sepia officinalis L (Mollusque Céphalopode)

Abstract: The cuttlefish, Sepia officinalis L., liver was investigated by histochemical and microanalytical methods. The greater part of the accumulated Cu is concentrated in spherulae which are elaborated by the basal cells. Cu is associated with both Ag and Zn. Fe is also found but the digestive cells are the most important site of Fe storage. Our data show that the spherulae are made of metallothionein-like proteins. The occurrence of these metal-binding proteins has ecological effects. The metals are easily assimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…These granules function in the storage and excretion of essential and non-essential metals, and their production is common in all major phyla (Brown 1982, George 1982. Thus, the observed increase of total cadmium levels in the digestive gland of cephalopods, resulting in the storage of cadmium in an insoluble form rather than via binding to cytosolic proteins, could be considered as more (Martoja & Marcaillou 1993). These authors suggested that the metals would be complexed by metallothioneins in these spherules.…”
Section: Discussionmentioning
confidence: 99%
“…These granules function in the storage and excretion of essential and non-essential metals, and their production is common in all major phyla (Brown 1982, George 1982. Thus, the observed increase of total cadmium levels in the digestive gland of cephalopods, resulting in the storage of cadmium in an insoluble form rather than via binding to cytosolic proteins, could be considered as more (Martoja & Marcaillou 1993). These authors suggested that the metals would be complexed by metallothioneins in these spherules.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of sulphydryl-rich proteins such as metallothioneins have been found in the cephalopod digestive gland (Tanaka et al 1983, Bustamante et al 2002b. Histochemical and microanalytical investigations in the digestive gland of the cuttlefish Sepia officinalis have shown that Ag is associated with Cu and Zn in spherules accumulated in the basal cells, and these spherules are composed of metallothionein-like proteins (Martoja & Marcaillou 1993). Metalloproteins play a major role in the homeostasis of Cu and Zn and are well known for their capacity to bind Ag, Cd and Hg (see e.g.…”
Section: Comentioning
confidence: 99%
“…These "phosphate granules" are easily observed with the light microscope and, interestingly, the presence of calcium has been demonstrated histochemically in tissue sections stained with the cobalt method (Marig6mez et al, 1986). On the other hand, calcium cells (Schoettli & Seiler, 1970;Marig6mez et al, 1986;Recio et al, 1988), and basal cells of cephalopods (Martoja & Marcaillou, 1993), which are also equivalent to basophilic cells (Marig6mez et al, 1995), can accumulate metals such as copper and zinc. In addition, metals other than calcium have also been localized in the phosphate granules of basophilic cells (Mason et al, 1984;Nott & Langston, 1989;Marig6mez et al 1990a).…”
Section: Discussionmentioning
confidence: 99%